Language accommodation and gender in Singapore English: a corpus-based approach looking at same-gender and mixed-gender interactions - Koh, Jia Jun (Nanyang Technological University, 2023)
Do men and women speak differently? Language differences between men and women have always been a popular topic across various cultures and languages. Singapore English is no exception but research on gendered interactions have received little attention in Singapore. This thesis utilises conversations extracted from Singapore’s National Speech Corpus (NSC), a three-part corpus of speech data produced by the Infocommunications and Media Development Authority of Singapore (IMDA), consisting of read scripts, local words, and dyadic interactions. These dyadic interactions will be viewed through the lens of Communication Accommodation Theory (CAT) and the Difference and Dynamic approaches in language and gender to examine how certain linguistic features that mark social distance are influenced by speaker gender and the dyad condition — i.e., same-gender dyads or mixed-gender dyads. The three linguistic features explored in this thesis are the use of backchannels, filled pauses, and Singlish particles, with an additional supplementary measure that employs the use of Language Style Matching (LSM) scores. Using linear mixed effects modelling, results show that speaker gender is a significant predictor for all three variables, with women using more backchannels than men, and men using more filled pauses and Singlish particles than women. For accommodation patterns from same-gender dyads to mixed-gender dyads, the use of backchannels diverged while the use of filled pauses and Singlish particles converged. Filled pauses and especially Singlish particles are shown to be good indicators of low social distance between interlocutors and reflect strategies used by both men and women to accommodate to each other. Results for LSM scores revealed that same-gender female dyads match more in linguistic style than same-gender male dyads, indicating the difference in communication styles between women and men — with women’s communication style being more cooperative than men’s. This study is the first quantitative analysis of linguistics features drawn from a large corpus of natural speech focusing on gender differences within the framework of CAT in Singapore. The findings give us a snapshot of how feminine and masculine speech styles are indexed in the Singapore context, and the usefulness of comparing same-gender and mixed gender dyads to provide an interactional dimension to the analysis.